Cultural Heritage and Cognitive Growth: Unraveling the Link Between Self-Efficacy and Mathematical Reasoning - Neni Iska, Zikri; Fitria Kautsari Azizah (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2025)
The purpose of this study was to explain and show how self-efficacy relates to the mathematical reasoning ability of sixth-grade students at SD Islam Kamila Insan Cita. This study used a quantitative method with a correlational design. The study took place at SD Islam Kamila Insan Cita and involved all 19 sixth-grade students. Data were collected using questionnaires and tests. To analyze the data and test the research hypothesis, the Pearson product-moment correlation formula was applied. The findings revealed a relationship between self-efficacy and mathematical reasoning ability among sixth-grade students of SD Islam Kamila Insan Cita. This conclusion is supported by the detected significance value, which is below the predetermined significance limit (0.001 <0.05), and the correlation coefficient of 0.688. The impact of variable X on variable Y is 47.33%, while the other 52.67% is influenced by various factors that are not examined.